Antioxidant capacity and kinetics of dendritic hindered phenols using DPPH assay. (July 2015) - Li, Cuiqin; Wei, Yujia; Shi, Weiguang; Wang, Jun; Wang, Baohui
Dendritic hindered phenols were synthesised using 3-(3, 5-di-tert-butyl-4-hydroxy-phenyl)-propionic acid and dendritic poly(amido-amine) (PAMAM) as materials. The structures of the dendritic hindered phenols were characterised by infrared spectroscopy (FTIR), 1 H-nuclear magnetic resonance spectroscopy ( 1 H NMR) and liquid chromatography–mass spectrometry (LC-MS). The scavenging capacity and kinetics of the dendritic hindered phenols were investigated using the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay. These dendritic hindered phenols have excellent scavenging capacity, being superior to antioxidants 1010 and 1098 with the same number of phenol hydroxyl groups. The scavenging capacity of the first-generation dendritic hindered phenol (1.0G dendritic phenol) was superior to that of the second-generation dendritic hindered phenol (2.0G dendritic phenol). The kinetic behaviour of the hindered phenols in scavenging the DPPH radical was a first-order reaction. The scavenging rate constants ( k 1 ) of the dendritic phenols with DPPH radical were higher than that of antioxidants 1010 and 1098, while the k 1 value of 1.0 G dendritic phenol was superior to that of 2.0 G dendritic phenol under the same test conditions. The scavenging activation energy ( E a ) of 1.0 dendritic phenol with four phenolic groups and two tertiary amine groups was the lowest, while that of antioxidant 1010 with a higher molecular weight and four phenolic groups was the greatest.